Women's Troubles: Painful Menstruation (Eurasian Medical Research Periodical, 2025)
This article presents general information, classification, clinical picture, diagnosis and treatment of dysmenorrhea. It also discloses age characteristics and the percentage of patients with dysmenorrhea.